1993
DOI: 10.2105/ajph.83.7.948
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in the elderly's use of medical procedures and diagnostic tests.

Abstract: OBJECTIVES. This study sought to examine racial differences in the use of medical procedures and diagnostic tests by elderly Americans. METHODS. We used 1986 physician claims data for a 5% national sample of Medicare enrollees aged 65 years and older to study 32 procedures and tests. For each service, we calculated the age- and sex-adjusted rate of use by race and the corresponding White-Black relative risk. RESULTS. Whites were more likely than Blacks to receive 23 services, and for many of these services, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
146
3

Year Published

1994
1994
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(156 citation statements)
references
References 37 publications
7
146
3
Order By: Relevance
“…One recent analysis of Medicare data [22] found that African American and low-income patients were less likely to have ambulatory physician visits, mammograms, and influenza immunizations, but that such individuals were more likely to be hospitalized or to die. Similarly, Escarce and colleagues [23] found that elderly whites were more likely than were elderly African Americans to receive 23 different procedures and tests, with whites receiving more and newer services or those requiring higher technology. Rosenheck, Fontana, and Cottrol [48] found that African American veterans who were provided mental health services from white clinicians received fewer services.…”
Section: Brief Background Of the Usphs-tuskegee Syphilis Study And Rementioning
confidence: 95%
See 2 more Smart Citations
“…One recent analysis of Medicare data [22] found that African American and low-income patients were less likely to have ambulatory physician visits, mammograms, and influenza immunizations, but that such individuals were more likely to be hospitalized or to die. Similarly, Escarce and colleagues [23] found that elderly whites were more likely than were elderly African Americans to receive 23 different procedures and tests, with whites receiving more and newer services or those requiring higher technology. Rosenheck, Fontana, and Cottrol [48] found that African American veterans who were provided mental health services from white clinicians received fewer services.…”
Section: Brief Background Of the Usphs-tuskegee Syphilis Study And Rementioning
confidence: 95%
“…Similarly, the clear evidence that African Americans frequently receive lower quality care from the health care system than do whites [22,23] is another factor potentially leading to distrust in the health care system and, in turn, to distrust of health care researchers. For example, although coronary heart disease (CHD) is the leading cause of death for African Americans in the United States [24,25], and cardiac revascularization procedures are well-established treatments for cardiovascular disease [26,27], a smaller proportion of African American patients than white patients receive such procedures in Veterans Administration (VA), Medicare, and other populations [28][29][30][31][32][33].…”
Section: Brief Background Of the Usphs-tuskegee Syphilis Study And Rementioning
confidence: 99%
See 1 more Smart Citation
“…11,12 In addition, it has been noted that blacks have lower rates than whites of utilization of high-technology cardiology services including coronary angiography, angioplasty, and revascularization, [13][14][15][16] as well as other cardiovascular treatments. [17][18][19] It has also been suggested that fatal cardiovascular disease in blacks involves less atherosclerosis of the epicardial coronary arteries than among whites. 7 Most of what is known about the effects of hypertension on mortality in blacks versus whites is based on information derived from epidemiological studies, clinical trials of drug treatment, or anecdotal clinical experience.…”
mentioning
confidence: 99%
“…1 Flow chart of participation in senior medical student survey regional differences in recommendations. 33,34 To search for similar geographic patterns in our findings, we grouped students by the Association of American Medical Colleges (AAMC) approach to regional grouping of states: Northeast, South, Central, and West (Appendix). 35 We also used each school's self-description (obtained from its website) as "public" or "private" to categorize the schools.…”
Section: Methodsmentioning
confidence: 99%